Analysis of the use of digital technologies at enterprises of the shipbuilding industry of the military-industrial complex - Lipatnikov Vitalii; Smirnova Ol'ga; Lebedkin Pavel (π-Economy)
The objective of the study was to analyze the features of using digital technologies to improve the activities of Russian shipbuilding enterprises. The main issue under consideration was the insufficient digitalization of enterprises of the military-industrial complex (MIC), as well as the need for the sovereignty of domestic software within this industry. The study analyzed the publications by leading domestic and foreign authors who studied various features related to the topic of digital transformation both in industrial enterprises in general and in shipbuilding. The study used a methodology that includes strategic, systemic and research approaches. Its purpose was to analyze the structure of digitalization of shipbuilding enterprises of the MIC at present and to identify key aspects of this process. According to the results obtained, the effectiveness of various software products in the operational activities of enterprises of MIC became clear. The key features of using various software products were identified, their characteristics were given, and a comparative review of the digital technology market was made. The use of digital solutions in the MIC covers three aspects at once: the properties and quality of the final product, the production process and warehousing. The introduction of various digital products made it possible to predict the final performance characteristics of the manufactured product. To do this, its digital twin was created by transferring data on its calculated physical, chemical and dimensional parameters to the digital environment. The use of digital products in production allows one to anticipate possible problems in the production process. Digital modeling of the product path from production to release to the market makes it possible to optimize processes even before the start of physical work, which reduces costs associated with product defects. The introduction of digital technologies in warehouses and supply chain management allows one to monitor balances in real time and purchase the necessary materials without the direct presence of a person. The need for centralized state support for the digitalization of control systems in the MIC is also separately noted.